Habermas the discourse theory of law and democracy - Baxter, Hugh. (Stanford, Calif. : Stanford Law Books, 2011)
This work bridges the gap between legal experts and those without special legal training, critically assessing the attempt of an unquestionably pre-eminent philosopher and social theorist to engage the world of law.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Habermas, Jürgen.; Law -- Philosophy; Sociological jurisprudence; Democracy -- Philosophy; Discourse analysis; Law; Jurisprudence & general issues; Methods, theory & philosophy of law